Studies of early pregnancy-induced transcripts in peripheral blood immune cells in cattle - Rocha, Cecília Constantino (2019)
In cattle, the largest part of embryonic loss occur during the first three weeks of pregnancy. Thus, to study and detect those loses as early as possible some points are key to improve reproductive efficiency. Half of the genetic material of the conceptus is allogenic to the maternal immune system. In this regard, the elucidation of the immune events is important during early pregnancy. Moreover, that moment is coincident with the release by the conceptus of the main glycoprotein signal, interferon-τ (IFN-τ). Interferon-τ is released in the circulation and stimulates some genes (ISGs). The study of the expression of the most common ISGs (ISG15, OAS1, MX1 e MX2) in immune cells has already been used before as an early pregnancy diagnosis, however, the accuracy was low. Therefore, considering the deficiency of studies on the immunology of pregnancy we tested the follow hypotheses: (1) at day 18 of pregnancy, novel genes beyond the traditional ISGs would be differentially expressed (DE) in immune cells of pregnant and non-pregnant heifers, which would allow the selection of potential pregnancy markers before day 20. Also, (2) the DE genes discovered would be linked with pathways of the immune response, which would be differentially expressed between animal parity categories and regulated in subspecies (Taurus and indicus). This dissertation consists of two studies. The first study was designed to detect novel genes by RNA sequence (RNAseq). Peripheral blood mononuclear cells (PBMC) RNA from day 18 post-fixed timed artificially inseminated (AI) Nelore heifers was subject to RNAseq. The transcripts profile was evaluated in PBMC and peripheral blood polimorphonuclear cells (PMN) among days 10 to 20 by qPCR. In summary, 9 and 5 out of the 20 genes evaluated were considered potential pregnancy markers in PBMC and PMN respectively. In the second study, the RNAseq results were submitted to enrichment analysis (GO, KEGG, and pathway score regulation) to elucidate the main pathway regulated in early pregnancy. The genes found were evaluated in whole blood from Holstein cows and heifers on D16, 19 and 23 post AI. Another in vitro experiment was performed to test if the genes linked to the pathway were stimulated by IFN-τ. For this purpose, uterine explants were cultured with mammalian medium with no supplementation, with PBS, and with recombinant IFN-τ, for 2 and 24 hours. As a result, the most significant pathway was linked with the pattern recognition receptors (PRRs). Eighteen genes were evaluated and seven of them showed an interaction between pregnancy status, animal category and time. Where for that seven genes on D23 the P-HF had a greater expression than NP-HF. All seven genes belong to the Toll like or Nod like receptors pathway. However, the in vitro results showed and effect of culture for all groups and we could not concluded if the regulation was mediated only by IFN-τ. In conclusion, early pregnancy induces differential changes on the immune system of beef and dairy heifers, compared with cows. The difference became obvious specially during the post implantation period (D23). In summary, we accepted the hypothesis that novel transcripts beyond the traditional ISGs could potentially be used as pregnancy markers and that the main pathway during early pregnancy in immune cells is linked with the immune response, which is regulated between subspecies and differentially expressed between parity category.